Legal Analysis of The Element of Economic Loss to The State in Article 2 Paragraph (1) and Article 3 of The Corruption Crimes Act - Munawwar Hamidi; Ida Keumala Jeumpa; Sri Walny Rahayu (International Journal of Law and Society, 2026)
The ambiguity of the concept of state economic loss in Article 2 paragraph (1) and Article 3 of the Corruption Crime Law (Tipikor Law) has yet to be defined normatively or by an official institution with the authority to do so. This uncertainty has given rise to legal problems in law enforcement, especially after Constitutional Court Decision No. 25/PUU-XIV/2016, which changed the qualification of corruption offenses to material offenses, so that the proof of economic loss to the state must be actual loss. However, in practice, as in the Surya Darmadi corruption case, law enforcement officials still face difficulties in determining the measure and method of proving economic loss to the state in a lawful manner. The issues in this study are the basis for the judge's consideration of the element of economic loss to the state in the Central Jakarta District Court Decision No. 62/Pid.Sus-TPK/2022/PN.Jkt.Pst and the obstacles and constraints in proving the element of economic loss to the state in criminal acts of corruption.This study uses a normative legal method with a statute approach, a case approach, and a conceptual approach. The results of the study show that the first-level panel of judges assessed that environmental damage and the loss of potential state revenue due to the illegal conversion of forest areas were part of the actual economic loss to the state, while the Supreme Court emphasized the importance of limiting this element to actual loss in accordance with Constitutional Court Decision No. 25/PUU-XIV/2016. The obstacles and constraints in proving the element of state economic loss in corruption crimes stem from internal and external factors that are interrelated and affect the effectiveness of law enforcement.